Hepatitis B antigen (HBsAg) in wildcaught Triatominae in Brazil: communication - Candeias, J. A. N. (1976)
A total of 890 impressions on filter paper identified as containing human blood, were examined for the presence of hepatitis B antigen (HBsAg), using the Hepanosticon haemagglutination and radioimmunoassay techniques. The samples examined belong to the Panstrongylus, Rhodnius and Triatoma genres. The Hepanosticon haemagglutination technique showed that 7 impressions, after elution, were presumably positive for HBsAg, but by radioimmunoassay, this antigen could only be detected in 1. The positive sample was obtained from a specimen of Triatoma sordida (fifth instar nymph).